3
$\begingroup$

$a_n=\frac{1}{2n}\sqrt[n]{1^n+2^n+...+(2n)^n}$

I think that $\sqrt[n]{1^n+2^n+...+(2n)^n}\rightarrow 2n+1$

So $a_n=\frac{2n+1}{2n}\rightarrow 1$

Any ideas if that's correct? And if so how do I prove it?

$\endgroup$
2
  • $\begingroup$ I guess my first question is how did you get $2n+1$? $\endgroup$ Sep 16 '18 at 16:59
  • $\begingroup$ Correct. By the way, your answer is the only one that show the FINAL RESULT $\displaystyle\left( one, 1\right)$. $\endgroup$ Sep 16 '18 at 17:06
16
$\begingroup$

Use the fact that $$ (2n)^n \leq 1^n+2^n+...+(2n)^n \leq 2n(2n)^n $$ and the squeeze theorem.

$\endgroup$
2
  • $\begingroup$ Nice and simple.............+1 $\endgroup$ Sep 16 '18 at 17:01
  • $\begingroup$ Very nice thank you very much! $\endgroup$
    – VakiPitsi
    Sep 16 '18 at 17:12
1
$\begingroup$

Hint. For $j,n\in \Bbb Z^+$ we have $$\quad\int_{j-1}^jx^ndx<j^n<\int_j^{j+1}x^ndx.$$ Now sum from $j=1$ to $j=2n.$

$\endgroup$
1
$\begingroup$

We have \begin{align} a_n=& \frac{1}{2n}\sqrt[n]{1^n+2^n+...+(2n)^n} \\ =&\frac{1}{2n}\sqrt[n]{(2n)^n\left[\frac{1^n}{(2n)^{n}}+\frac{2^n}{(2n)^{n}}+...+\frac{(2n-1)^n}{(2n)^{n}}+1\right]} \\ =&\sqrt[n]{\frac{1^n}{(2n)^{n}}+\frac{2^n}{(2n)^{n}}+...+\frac{(2n-1)^n}{(2n)^{n}}+1} \\ =&\sqrt[n]{\left(\frac{1}{2n}\right)^{n}+\left(\frac{2}{2n}\right)^{n}+...+\left(1-\frac{1}{2n}\right)^{n}+1} \end{align} For $ n $ big enough we have $$ 0\leq \left(\frac{1}{2n}\right)^{n}\leq 1, \quad 0\leq \left(\frac{2}{2n}\right)^{n} \leq 1,\ldots \qquad \ldots, 0\leq \left(1-\frac{1}{2n}\right)^{n}\leq 1. $$ It is easy to see that $$ \sqrt[n]{0+0+\ldots+0+1}\leq a_n \leq \sqrt[n\,]{\underbrace{1+1+\ldots+1+1}_{n \mbox{ times }}} $$ or $$ 1\leq a_n\leq \sqrt[n]{n} $$ Once $\sqrt[n]{n}\to 1$, thus $a_n\to 1$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.